The contribution of local wisdom integrated science learning model to the students scientific communication skill on ecology learning - Mochammad Yasir; Ana Yuniasti Retno Wulandari; Nur Qomaria; Binar Kurnia Prahani; Aushia Tanzih Al Haq (Universitas Ahmad Dahlan, 2020)
Science learning can be integrated with local culture in the form of learning models. This study aimed to analyze the contribution of the local wisdom integrated science (LWIS) learning model in practicing scientific communication skills of prospective science teachers in Ecology learning. This study used a quasi-experimental of posttest only control design and purposive sampling technique from prospective science teachers at Trunojoyo University, Madura. The research instrument was a test of scientific communication skills, observations of the implementation of the LWIS learning model, questionnaire and interview responses of prospective science teachers to ecological learning using the LWIS learning model. Data analysis techniques used the t-test significance level of 5%. The results showed that (1) there were differences in the scientific communication skills of prospective science teachers after using the LWIS learning model of significance of 0.014 < 0.05 and - tcount < ttable < tcount (-2.528 < 1.9996 < 2.528), (2) scientific communication skills in the experimental class by 94.87% (high) > control class by 88.03% (high), (3) implementation of the LWIS learning model obtained an average value of 100% (very good), and (4) the response of prospective science teachers obtained an average value of 89.40% (very good) for the experimental class and the prospective science teacher said that the learning model was new, easy to use, developed scientific communication skills. Thus it can be concluded that the LWIS learning model contributes positively in training the scientific communication skills of prospective science teachers in Ecology learning.